Genesis of Pb-Zn-Cu-Ag Deposits within Permian Carboniferous-Carbonate Rocks in Madina Regency, North Sumatra - Harahap, Bhakti Hamonangan; Abidin, Hamdan Zainal; Gunawan, Wahyu; Yuniarni, Rum (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.3.167-184Strong mineralized carbonate rock-bearing Pb-Zn-Cu-Ag-(Au) ores are well exposed on the Latong River area, Madina Regency, North Sumatra Province. The ore deposit is hosted within the carbonate rocks of the Permian to Carboniferous Tapanuli Group. It is mainly accumulated in hollows replacing limestone in the forms of lensoidal, colloform, veins, veinlets, cavity filling, breccia, and dissemination. The ores dominantly consist of galena (126 000 ppm Pb) and sphalerite (2347 ppm Zn). The other minerals are silver, azurite, covellite, pyrite, marcasite, and chalcopyrite. This deposit was formed by at least three phases of mineralization, i.e. pyrite and then galena replaced pyrite, sphalerite replaced galena, and pyrite. The last phase is the deposition of chalcopyrite that replaced sphalerite. The Latong sulfide ore deposits posses Pb isotope ratio of 206Pb/204Pb = 19.16 - 20.72, 207Pb/204Pb = 16.16 - 17.29, and 208Pb/204Pb = 42.92 - 40.78. The characteristic feature of the deposit indicates that it is formed by a sedimentary process rather than an igneous activity in origin. This leads to an interpretation that the Latong deposit belongs to the Sedimentary Hosted Massive Sulfide (SHMS) of Mississippi Valley-Type (MVT). The presence of SHMS in the island arc such as Sumatra has become controversial. For a long time, ore deposits in the Indonesian Island Arc are always identical with the porphyry and hydrothermal processes related to arc magmatism. This paper is dealing with the geology of Latong and its base metal deposits. This work is also to interpret their genesis as well as general relationship to the regional geology and tectonic setting of Sumatra.